Generation and Characterization of a Foxtail Millet (Setaria italica) Mutant Library - Sun, Jing; Luu, Ngoc Sinh; Chen, Zhenhua; Chen, Bing; Cui, Xuean; Wu, Jinxia; Zhang, Zhiguo; Lu, Tiegang (Frontiers in Plant Science, 2019)
Foxtail millet (Setaria italica) is attractive to plant scientists as a model plant because of several distinct characteristics, such as its short stature, rapid life cycle, sufficient seed production per plant, self-compatibility, true diploid nature, high photosynthetic efficiency, small genome size, and tolerance to abiotic and biotic stress. However, the study on the genetic resources of foxtail millet largely lag behind those of the other model plants such as Arabidopsis, rice and maize. Mutagenized populations can not only create new germplasm resources, but also provide materials for gene function research. In this manuscript, an ethyl methanesulfonate (EMS)-induced foxtail millet population comprising ~15,000 individual M1 lines was established. Total 1353 independent lines with diverse abnormal phenotypes of leaf color, plant morphologies and panicle shapes were identified in M2. Resequencing of sixteen randomly selected M2 plants showed an average estimated mutation density of 1 loci/213 kb. Moreover, we provided an example for rapid cloning of the WP1 gene by a map-based cloning method. A white panicle mutant, named as wp1.a, exhibited significantly reduced chlorophyll (Chl) and carotenoid contents in leaf and panicle. Map-based cloning results showed an eight-base pair deletion located at the sixth exon of wp1.a in LOC101786849, which caused the premature termination. WP1 encoded phytoene synthase. Moreover, the sequencing analysis and cross test verified that a white panicle mutant wp1.b was an allelic mutant of wp1.a. The filed phenotypic observation and gene cloning example showed that our foxtail millet EMS-induced mutant population would be used as an impotrant resource for functional genomics studies of foxtail millet.